Experimental evaluation of the surfactant adsorptions performance on coal particles with different properties - Chang, Ping; Xu, Guang; Chen, Yinping; Liu, Y. (2022)
The prevalence of Coal Workers’ Pneumoconiosis (CWP) increased with the increasing coal production. Currently, water spray is a commonly used method to control coal dust in underground coal mines. However, coal dust is well known for its hydrophobic property. Due to this, it is challenging in underground mines to suppress coal dust concentration to regulatory limits, thus, thousands of miners are under the threat of CWP caused by the high coal dust concentration. Surfactants aid water spray are believed an effective method to lower coal dust concentration. In this study, zeta potential and adsorption of three types of surfactants on coal particles with different ranks and particle sizes were studied. It was confirmed that the coal surface was negatively charged and the zeta potential of coal particles was changed based on the addition of surfactant type. In SDBS and CTAB, the lower rank coal particles showed lower zeta potential and the finer coal particles possessed the larger zeta potential, while opposite results were found in TX100. The lignite adsorbed more SDBS and less TX100 than subbituminous and anthracite, but anthracite adsorbed the most amount CTAB at a higher concentration. The finer coal particles adsorbed the more surfactant amount for all the surfactants at each concentration. Increasing temperature help to improve all the surfactant adsorption capacity but failed to lift all the coal particles’ zeta potential at the tested surfactant concentrations. Adding salts increased the SDBS adsorption but no obvious improvement was found for the other two surfactants.